2016
DOI: 10.4103/0972-2327.173302
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for acute ischemic stroke in pregnancy using the penumbra system

Abstract: Even though intravenous thrombolysis with tissue plasminogen activator (IV tPA) is the standard of care in acute ischemic stroke, its use in pregnancy is not clearly defined. Mechanical thrombectomy devices can be an option; however, literature on the use of such mechanical devices in stroke in pregnancy is lacking. Here we describe two cases that developed acute embolic stroke during pregnancy who were successfully treated by mechanical clot retrieval using the Penumbra system 28 (Penumbra Inc., Alameda, Cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Aaron et al described two cases of MCA occlusion treated with endovascular thrombectomy only through aspiration by the Penumbra system. 20 Bhogal et al reported a case of MCA occlusion treated by stent retriever thrombectomy and a basilar artery occlusion treated by combined reperfusion therapy. 14 The outcome was good for both the mothers and children in these four cases, emphasizing the benefit of this treatment approach in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Aaron et al described two cases of MCA occlusion treated with endovascular thrombectomy only through aspiration by the Penumbra system. 20 Bhogal et al reported a case of MCA occlusion treated by stent retriever thrombectomy and a basilar artery occlusion treated by combined reperfusion therapy. 14 The outcome was good for both the mothers and children in these four cases, emphasizing the benefit of this treatment approach in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…To date only 2 cases of mechanical thrombectomy for thromboembolic stroke have been published [20]. Aaron et al [20] recently published 2 cases of women, both of whom were in their 20s and in the 3rd trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Aaron et al [20] recently published 2 cases of women, both of whom were in their 20s and in the 3rd trimester. One patient had undergone a previous mitral valve replacement, and her normal oral anticoagulants had been switched to low-molecular-weight heparin.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of systemic thrombolysis with tissue plasminogen activator as well as endovascular therapy in acute ischemic stroke is well documented [1]. Furthermore, recent studies have documented that thrombolysis followed by thrombectomy using a stent retriever in patients with acute ischemic stroke in the proximal anterior intracranial circulation is superior to thrombolysis alone [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, pregnant women with acute ischemic stroke have been excluded from reperfusion trials, resulting in paucity of evidence within this area [5]. The concerns regarding the use of thrombolysis during pregnancy include the risk of placental abruption, retroplacental hemorrhage, abortion, peripartum uterine bleeding and postpartum hemorrhage, as well as possible teratogenicity of thrombolysis treatment [1, 6, 7]. The use of thrombectomy during pregnancy raises concerns regarding radiation, anesthesia related complications, and the use of contrast during the procedure [8, 9].…”
Section: Introductionmentioning
confidence: 99%